Dental unit waterlines in Israel: evidence of widespread microbial contamination and a need for national regulation - Luda Groisman; Eti Burla; Daniel Kushnir; Shereen Assaly; Roni Gat; Efrat Rorman; Shoshanit Ohad; Ehud Kaliner (Israel Journal of Health Policy Research, 2026)
Abstract Background Dental unit waterlines (DUWLs) are susceptible to microbial contamination because of biofilm formation within their complex water delivery systems. Although the US CDC and several professional organizations recommend maintaining dental treatment water at potable water quality, Israel currently lacks specific national standards and regulatory requirements for monitoring and maintaining DUWLs. This study assessed the prevalence of Legionella and other microbial contaminants in DUWLs across dental clinics in central Israel and examined factors associated with contamination to inform patient and dental stuff safety and national policy development. Methods This survey included 52 randomly selected dental clinics, with 359 water samples collected from DUWL components and water sources. Samples were tested for Legionella spp., Legionella pneumophila , Pseudomonas aeruginosa , and heterotrophic plate count (HPC). Water quality indicators - residual chlorine and turbidity were also measured. Statistical analyses were used to explore associations between microbial and common water quality and clinic characteristics. Results Of the clinics tested, 94% exhibited at least one abnormal water quality result. Legionella exceeded the threshold in 74% of samples, Pseudomonas in 25%, and HPC in 53%. Contamination was most frequent in turbine and syringe connectors. Low chlorine levels and high turbidity were significantly associated with increased microbial counts. Legionella pneumophila concentrations above 2,500 GU/L were found in 19% of Legionella -positive samples. No consistent effect of dental chair age or clinic operating frequency was observed. Conclusions The widespread microbial contamination identified in Israeli dental unit waterlines represents a potential patient and occupational health concern and highlights an important regulatory gap in the oversight of dental water quality. These findings support the need to develop national standards for DUWL monitoring, maintenance, and treatment, together with routine surveillance and regulatory oversight, to improve patient safety and ensure safe dental care environments.